Experimental Investigation on Composite Deck Slab Made of Cold-Formed Profiled Steel Sheeting - Saavedra-Flores, E; Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
An experimental investigation is performed on various cold-formed profiled sheets to study the connection behavior of composite deck slab actions using bolted shear connectors. Various profiles like dovetailed (or) re-entrant profiles, rectangular profiles and trapezoidal profiles are used in the present investigation. This experimental investigation deals with the evaluation of various parameters such as the ultimate load carrying capacity versus deflection, load versus slip, ductility ratio, strain energy and modes of failure in composite slab specimens with varying profiles. From the test results the performance of dovetailed profiled composite slabs’ resistance is significantly higher than the other two profiled composite deck slabs. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.